Using Differentiated Learning Activities to Improve Student's Grammatical Competence - Roushiell France London (PT FORMOSA CENDEKIA GLOBAL, 2022)
The study assessed the grammatical competence and learning styles of Grade 7 students and was a basis for developing differentiated language learning activities as an intervention that matched students’ learning styles based on Flemmings and Mill’s VARK learning style. Information about their competence in grammar were obtained through a pre-test and post-test. The assessment on morphology focuses on root words and affixation and while syntax focuses on the verb tenses, subject-verb agreement, prepositions and pronouns. Results from the posttest suggested that students who were given an intervention through the use of differentiated learning activities performed better compared to their scores during their pre-test. Results also showed that students responded well to the different activities that were aligned to their preferred learning styles.